Feasibility of Using Ultrasound-Assisted Biodiesel Production from Degummed-Deacidiﬁ ed Mixed Crude Palm Oil Using Small-Scale Circulation - Somnuk, Krit; Smithmaitrie , Pruittikorn; Prateepchaikul, Gumpon (Agriculture and Natural Resources, 2012)
A transesteriﬁ cation reaction of degummed-deacidiﬁ ed mixed crude palm oil (DDMCPO) with methanol in the presence of alkali-catalyst NaOH was performed in a 400 W small-scale ultrasonic circulation process at a low frequency of 20 kHz with an input capacity of 4 × 100 W. The various parameters used were methanol (16, 23 and 30% by volume) and a base catalyst of 3, 5 and 7 g NaOH per liter of oil. The results of the fatty acid methyl ester (FAME) conversion with and without ultrasonic irradiation assistance were compared and showed that the maximum FAME conversion of 92.5% by weight could be achieved with 7 g NaOH per liter of oil and 23% by volume methanol with a reaction temperature of 45 oC and a total residence time of more than 6 min. Furthermore, these conditions were used to compare the effect of FAME conversion with and without the ultrasonic irradiation. The results clearly indicated that circulation of the mixture using ultrasound energy had more signiﬁ cant potential in the conversion of oil to FAME than the circulation of the mixture through the reactor without ultrasound energy. Consequently, the use of ultrasound irradiation can reduce the reaction time and increase the FAME conversion.